Firm and Worker Responses to Extensions in Paid Maternity Leave - Cecilia Machado; Valdemar Neto; Christiane Szerman (Institute of Labor Economics (IZA), 2023)
This paper investigates how firms and workers respond to a voluntary government-funded program increasing the duration of paid maternity leave from four to six months in Brazil. We show that larger, higher-paying, and more productive firms are more likely to provide extended leaves to workers. Exploiting the gradual implementation of extended leave across firms and the exact time of leave-taking, we present four key findings. First, we find an incomplete take-up of 35 percent among eligible workers, largely driven by those with high socioeconomic status. Second, firms and workers strategically defer job separations to extract rents from the government. Third, extended leave has no long-term impact on maternal labor market outcomes. Fourth, job security and information transmission about leave extensions boost take-up and reduce deferred job separations. The results illustrate that distributional concerns can justify the mandated provision of extensions in paid maternity leave.
Keywords: J13; J22; J32; 330; maternity leave; labor market; social protection